Communication with a Sick Person and at the End of Life – Therapeutic Importance - Rozen, Barbara (Studia Warmińskie, 2021)
The article is an attempt to answer the question: How to improve the quality of life of a sick person who is at the end of his life through proper communication? Any help will not be effective enough without establishing a good relationship with the person in need of help. The key issue is the ability to establish a friendly or even therapeutic relationship with such a person. Proper communication facilitates the person’s understanding and cooperation, and can motivate him to respect medical recommendations. Responsibility for the course of communication lies primarily with the person who wants to provide this support, therefore, first of all, it is the person who must be aware of the obstacles and errors in communication that may occur and that should be avoided. They have been discussed in the article. It is essential to try to understand people in such a difficult life situation as illness or old age. Therefore, the typical psychological experiences of people in such a situation, their mental and spiritual needs, and the possibilities of dealing with them are discussed. The key part of the article is to discuss the determinants of supportive communication based on affirmation, mindfulness and sensitive response, respecting the already rich knowledge about communication with the sick and the elderly. Listening and understanding are the keystones of the helping and supporting relationship.